Pengaruh Persepsi Harga dan Pengalaman Pelanggan Terhadap Minat Beli Pada Layanan ShopeeFood: (Studi Pada Pengguna di Kota Medan) - Claudia Yonica Tampubolon; Feronica Simanjorang; Onan Marakali Siregar (Cantaka: Jurnal Ilmu Ekonomi dan Manajemen, 2025)
Consumer’s purchase intention in food delivery services is increasingly influenced by price perception and customer experience, particularly amid the intense competition between ShopeeFood, GoFood, and GrabFood in Medan. A fair price perception and a positive customer experience can enhance consumers’ intention to make purchases. This study aims to analyze the effect of price perception and customer experience on purchase intention in ShopeeFood services in Medan. Both variables were tested partially and simultaneously to determine the extent of their impact on consumers’ purchase intention. The research employed a quantitative approach with an associative research type. The population in this study consisted of people in Medan who know and are interested in using ShopeeFood. The sample approach used in this study was probability sampling specifically simple random sampling, resulting in 97 respondents calculated with the Cochran formula. Primary data were collected through questionnaires, while secondary data were obtained from literature studies. The data analysis methods included validity tests, reliability tests, classical assumption tests, multiple linear regression analysis and hypothesis testing. The findings indicate that, partially, price perception has a positive and significant effect on purchase intention. Customer experience also has a positive and significant effect on purchase intention. Simultaneously, both variables significantly influence purchase intention among ShopeeFood users in Medan. The correlation coefficient (R) of 0.672 or 67% shows a strong relationship between price perception and customer experience on purchase intention. Furthermore, the Adjusted R Square value indicates that both variables contribute 44.1% to purchase intention, while the remaining 55.9% is influenced by other factors not examined in this study.